Pengembangan Sistem Informasi Manajemen ASN (SIMAS) Online Badan Kepegawaian Daerah Kota Malang - Citra Putri Adiyanti; Fajar Pradana; Widhi Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The Regional Personnel Agency (BKD) of Malang is the overshadowed body in the data management of all Civil Servants (PNS) in Malang. The main problem currently being faced by BKD Malang is that the process of submitting letters from civil servants is still ineffective. The reason for this is because every file submitted by PNS to each work unit and to the BKD directly is still in the form of paper documents, for example a copy. This causes the BKD still has to do the process of scanning every file submitted by the PNS so that it slows down the documentation process and the process of submitting the legalization of the submission of letters to the leadership. So that causes the length of the process of approving each of the problems raised by civil servants. The current submission process can be completed with an average period of one to 2-6 months. From these problems SIMAS will be developed to facilitate the process of submitting letters by way of civil servants can directly upload digital documents to speed up the process of submitting the required documents. Submissions that exist in this system are Submission of Periodic Salary Increase, Employee Card, Husband / Wife Card, and Model C. From the process of needs analysis, 55 functional requirements and 1 non-functional need will be obtained. After the design and implementation process will be carried out testing will be carried out by testing whitebox and blackbox for functiounal requirements and testing competibility testing for testing non-functiounal requirements. Whitebox testing consists of unit testing to test three methods that produce valid valuus ​​on all existing test pathways and integration testing to test two integrated methods and produce valid values ​​on all existing test paths. Blackbox testing will be done by testing validation of 55 functional requirements and producing valid values ​​in all test cases so that the sistem can run well and as expected. Compatibility testing is done useng the Sortsite tool and produces that the sistem can run properly on various browsers and there are no results that have critical issues.